The impact of restaurant service on customer satisfaction: a case of restaurant industry in Kelantan - Lee, Heng Ee; Ismail, Noorulfarahiah; Hamsah, Nurul Kamalia (2015)
The customer satisfaction is very important in the restaurants industry as to retain the customer loyalty towards the restaurant. Food quality, price of food, service quality and the restaurant atmosphere are the factors that had been focusing to identify the relationship with the customer satisfaction towards the restaurant industry. The objective of this study is to examine the impact of restaurant service on customer satisfaction a case of restaurant industry in Kelantan. Secondary research and quantitative method were used to enlighten the concept of customer satisfaction. The data was analysed by using the stratified random sampling, the correlation and multiple regressions were used by SPSS-22 to test the model. This research also includes past research about the factors affected customer satisfaction while focusing on Kelantan restaurant industry.